Effect of opioid-free anesthesia on the incidence of postoperative nausea and vomiting: A meta-analysis of randomized controlled studies - Zhang, Yanan; Ma, Dandan; Lang, Bao; Zang, Chuanbo; Sun, Zenggang; Ren, Shengjie; Chen, Huayong (Medicine (Baltimore), 2023)
Background: Research on opioid-free anesthesia has increased in recent years; however, it has never been determined whether it is more beneficial than opioid anesthesia. This meta-analysis was primarily used to assess the effect of opioid-free anesthesia compared with opioid anesthesia on the incidence of postoperative nausea and vomiting. Methods: We searched the electronic databases of PubMed, the Cochrane Library, Web of Science and Embase from 2014 to 2022 to identify relevant articles and extract relevant data. The incidence of postoperative nausea and vomiting, time to extubation, pain score at 24 hours postoperatively, and time to first postoperative rescue analgesia were compared between patients receiving opioid-free anesthesia and those receiving standard opioid anesthesia. Differences in the incidence of postoperative nausea and vomiting were evaluated using risk ratios (95% confidence interval [CI]). The significance of the differences was assessed using mean differences and 95% CI. The heterogeneity of the subject trials was evaluated using the I2 test. Statistical analysis was performed using the RevMan 5.4 software. Results: Fourteen randomized controlled trials, including 1354 participants, were evaluated in the meta-analysis. As seen in the forest plot, the OFA group had a lower risk of postoperative nausea and vomiting than the control group (risk ratios = 0.41, 95% CI: 0.33-0.51, P < .00001; n = 1354), and the meta-analysis also found that the OFA group had lower postoperative analgesia scores at 24 hours (P < .000001), but time to extubation (P = .14) and first postoperative resuscitation analgesia time (P < .54) were not significantly different. Conclusions: Opioid-free anesthesia reduces the incidence of postoperative nausea and vomiting while providing adequate analgesia without interfering with postoperative awakening.